The Palaeozoic basement of the Andean Frontal Cordillera at 34º S (Cordón del Carrizalito, Mendoza Province, Argentina): Geotectonic implications - García-Sansegundo, J.; Farias, P.; Rubio-Ordóñez, A.; Heredia, N. (Journal of Iberian Geology, 2014)
The Cordón del Carrizalito is located in the southern sector of the Andean Frontal Cordillera. In this area, the Andean basement is composed of meta-sedimentary rocks (Las Lagunitas Formation) of Ordovician age. In addition, no- or very low grade metamorphism and less deformed rocks also occur in the study area. We call these rocks Selerpe series, whose characteristics are comparable to other series, late Carboniferous in age, described in nearby areas. The Las Lagunitas Formation is affected by west-verging folds, developed under low-grade metamorphic conditions. These structures can be attributed to the Chanic orogeny (Late Devonian – early Carboniferous). The Selerpe series and Las Lagunitas Formation are deformed by east-verging thrusts and folds developed in narrow bands and generated in the absence or under very low metamorphic conditions. These structures always deform the Chanic structures, and are attributed to the Gondwanan deformation (San Rafael orogeny, late Carboniferous – Permian in age). The Chanic structures of the study area can be placed in the western branch and in the hinterland of the Chanic orogen, which was developed as a result of the accretion of the Chilenia terrane at the west Gondwana margin during Late Devonian and early Carboniferous. The eastern branch of this orogen is located in the Andean Precordillera. The Permo-Triassic cover, deformed by the Andean orogenic cycle (Mesozoic – Cenozoic), rests unconformably on the Palaeozoic basement rocks.